Modeling the performance impacts caused by an earthquake to the construction industry: Case study on the 2010 Chile earthquake - Forcael, Eric; González, Vicente; Opazo, Alexander; Orozco, Francisco; Araya, Richard (Revista de la Construcción. Journal of Construction, 2017)
Natural disasters affect the construction industry in many ways other than the direct damages. This paper presents a model that evaluates the performance impacts caused by an earthquake to the construction industry by using the 2010 Chilean earthquake as case study. The main variables affected by a seismic event in construction companies and their relationships were modeled by means of the use of Partial Least Square (PLS). The modeling framework was developed by interviewing CEOs of construction companies located in areas affected by the earthquake. Then, a model of interrelationships, which would explain how variables are affected by an earthquake was developed. The main findings showed that when a severe telluric event occurs, the two most affected factors were Relationship with the Owner/Clients and Image, while the most affected indexes were Owner/Client Satisfaction and Financial Situation. Thus, this research emphasizes the importance of these four variables (factors and indexes), when the construction industry faces a large earthquake.